THE STABILITY OF BIOLOGICAL DIVERSITY TO ANTHROPOGENIC INFLUENCE (International journal of artificial intelligence, 2024)
The article examines biodiversity indicators and landscape ecotones as determinants of the stability of geosystems to anthropogenic impact. Additionally, criteria and approaches related to assessing biological and landscape diversity are analyzed.